Studi Komparasi Pengaturan Zina Dalam Kitab UndangundangHukum Pidana (Kuhp) Dan Rancangan UndangundangKitab Undang-Undang Hukum Pidana (Ruu Kuhp)2015 - Hartono, Wisnu Aditya; , Mutimatun Ni'ami, S.H., M.Hum; , Kuswardani, S.H., M.Hum (2016)
The current development, technology and culture are so quick nowaday, leading to new problems for legislators on how to protect people effectively and efficiently against the danger of demoralization as a result of perspectives, cultures and habits of foreign people/western people concerning seems like free sexual life. Morality damage which happen nowaday is because of the spreading adultery. Adultery is an sexual intercourse between a married person and a person who is not his or her spouse. Generally, adultery is not only when people do the sexual intercourse, but it is also every sexual activities leading to destroy human dignity. the adultery regulation in The Indonesian Criminal Code is provisioned on Article 284 section (1). It carries the maximum penalty is 9 (nine) months imprisonment. Whilst the regulation of adultery in The Draft Indonesian Criminal Code 2015 is provisioned on Article 483 section (1), the penalty for adultery offence carries a maximum penalty of 5 (five) years imprisonment.